ALK positive inflammatory myofibroblastic tumour of the pineal region. Issue 9 (26th August 2005) - Clarke, A J; Jacques, T S; Galloway, M J; Thom, M; Kitchen, N D; Plant, G T
Abstract : Inflammatory myofibroblastic tumours (IMTs) are an uncommon spindle cell neoplasm with a dense inflammatory infiltrate, usually encountered in children. IMTs of the central nervous system are extremely rare. This report describes the case of an IMT in a 61 year old man, in the pineal region. The tumour was completely excised, and immunohistochemistry demonstrated anaplastic lymphoma kinase 1 expression. There was no tumour recurrence during 18 months of follow up. Our case extends both the age range and sites of occurrence of this rare tumour.